2020
DOI: 10.1007/s11573-020-01012-x
|View full text |Cite
|
Sign up to set email alerts
|

“Big brother is watching you”: surveillance via technology undermines employees’ learning and voice behavior during digital transformation

Abstract: In the digital age, the ability of organizations to create innovation is more important than ever before. By taking an employee perspective to digital transformation, we examine two important and inter-related cornerstones of organizational innovation—employees’ intrinsically motivated learning (i.e., their learning orientation) and employees’ willingness to speak up and raise constructive suggestions (i.e., their voice behavior). We conducted a survey study with 100 employees working in industries that are cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 127 publications
1
12
0
Order By: Relevance
“…Trust may be a key factor that contributes to this variability (20). Nonetheless, the results suggest that people are generally open to the idea of using biosensors in the workplace, and also being part of the process to improve them.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Trust may be a key factor that contributes to this variability (20). Nonetheless, the results suggest that people are generally open to the idea of using biosensors in the workplace, and also being part of the process to improve them.…”
Section: Discussionmentioning
confidence: 89%
“…Potential User responses suggest that they are less sure about who owns the data and responded less uniformly that it should be the employee, compared to Implementers. Trust may be a key factor that contributes to this variability ( 20 ). Nonetheless, the results suggest that people are generally open to the idea of using biosensors in the workplace, and also being part of the process to improve them.…”
Section: Discussionmentioning
confidence: 99%
“…The commercial persuasion of self-interested companies offering algorithmic recommendations can also make consumers feel observed, thereby decreasing the consumers' perceived personal privacy; this has been reported to evoke feelings of threat to the customer's autonomy [64]- [66]. The feeling of being watched (e.g., surveilled) has also been linked to increases in strain and stress on humans [67], [68]. Many people who are living with physiological enervation are likely to be prone to making purchasing errors in product choices, and to be particularly prone to buying services that are perceived as too alluring to forego.…”
Section: Physiological Enervation and Online Addictions-who Or What I...mentioning
confidence: 99%
“…Learning goal-oriented people are inclined to seek self-development opportunities and perceive challenging tasks as learning opportunities; thus, they are more likely to value the potential benefits of speaking up and exert increased effort to offer suggestions, ideas, and opinions. Some scholars have noted that learning goal-oriented individuals are more likely to be engaged in extra-role behavior, such as voice behavior (Kensbock & Stöckmann, 2021 ; Ng & Lucianetti, 2018 ). Recently, Kensbock and Stöckmann ( 2021 ) also found that learning goal-oriented individuals are more engaged in voice behavior within organizations.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Some scholars have noted that learning goal-oriented individuals are more likely to be engaged in extra-role behavior, such as voice behavior (Kensbock & Stöckmann, 2021 ; Ng & Lucianetti, 2018 ). Recently, Kensbock and Stöckmann ( 2021 ) also found that learning goal-oriented individuals are more engaged in voice behavior within organizations.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%